ANALISIS POLA PENYAKIT DENGAN METODE ASSOCIATION RULE (STUDI KASUS : RSUD LABUANG BAJI) - Mintu, Yupita Febriani; Yusri, Iin Karmila; Saharuna , Zawiyah (Politeknik Negeri Ujung Pandang, 2024)
RSUD Labuang Baji has a lot of medical record data, but this medical record data has not been used optimally and has not been processed to produce useful information for Laburan Baji Hospital. In this study the data used were outpatient medical record data in 2019, by analyzing three attributes, namely disease diagnosis (ICD), gender, and age group. The method for conducting data analysis is the association rule method using the Apriori algorithm and Tools R. The results of this study are disease patterns using a minimum support value of 0.01 and a minimum confidence value of 0.6, and the disease pattern formed is an associative rule with a combination of 2k-itemset and 3k item set of 25 associative rules where the rules for this disease pattern have a lift ratio value of > 1, so this disease pattern can be used as a recommendation to improve hospital services.